Hydrothermal Pretreatment of Water-Extracted and Aqueous Ethanol-Extracted Quinoa Stalks for Enzymatic Saccharification of Cellulose - Cristhian Carrasco; Leif J. Jönsson; Carlos Martín (Energies, 2021)
Auto-catalyzed hydrothermal pretreatment (A-HTP) and sulfuric-acid-catalyzed hydrothermal pretreatment (SA-HTP) were applied to quinoa stalks in order to reduce their recalcitrance towards enzymatic saccharification. Prior to pretreatment, quinoa stalks were extracted with either water or a 50:50 (v/v) ethanol–water mixture for removing saponins. Extraction with water or aqueous ethanol, respectively, led to removal of 52 and 75% (w/w) of the saponins contained in the raw material. Preliminary extraction of quinoa stalks allowed for a lower overall severity during pretreatment, and it led to an increase of glucan recovery in the pretreated solids (above 90%) compared with that of non-extracted quinoa stalks (73–74%). Furthermore, preliminary extraction resulted in enhanced hydrolysis of hemicelluloses and lower by-product formation during pretreatment. The enhancement of hemicelluloses hydrolysis by pre-extraction was more noticeable for SA-HTP than for A-HTP. As a result of the pretreatment, glucan susceptibility towards enzymatic hydrolysis was remarkably improved, and the overall conversion values were higher for the pre-extracted materials (up to 83%) than for the non-extracted ones (64–69%). Higher overall conversion was achieved for the aqueous ethanol-extracted quinoa stalks (72–83%) than for the water-extracted material (65–74%).